Marketing of Indian inland open water fishes as 'green fish': strategies and policy options for efficient value chain - Pandit, Arun; Das, Basanta Kumar; Roy, Piyashi Deb (Journal of the Inland Fisheries Society of India, 2022)
The aquaculture sector is expanding at a fast pace to produce fish food for human consumption and turned into a profitable business activity. However, increased aquaculture production and its interaction with fisheries resources remain a concern and the environmental sustainability of the aquaculture sector is being challenged. The high input-high output production system involves application of lot of inputs including chemical fertilizers, pesticides, growth promoters etc. which left their footprints in the fish flesh which ultimately finds their way to human body. Fishes in the inland open waters like rivers, estuaries, reservoirs, floodplain wetlands, lagoons, backwaters are produced in a healthy and sustainable manner. Therefore, there exists a scope for entrepreneurship development in marketing of fishes produced in inland open waters which can be labeled and marketed as 'green fish'. This can be sold at price premium to the specific consumer groups. The proposed green fish shall strive to minimize biodiversity loss and environmental degradation while maximizing economic and social benefits in the lines of blue growth. The system will provide opportunities for rural entrepreneurship and lot of youths can be gainfully employed along the value chain.Key words Inland open waters; Marketing; Green fish